The doping critical attitude of elite sports coaches in combat sports - Pöppel, K.; Büsch, D. (German Journal of Exercise and Sport Research, 2019)
Youth coaches take a significant role in the athlete`s network and represent an influencing factor on doping prevention, which has been investigated insufficiently by empirical research in young elite sports. Especially, combat sports are characterized by a multitude of doping opportunities to enhance the chance of winning. In order to deduce an effective and efficient doping prevention within the setting of combat sports, which is acknowledged by the protagonists, an examination of the coaches` baseline concerning doping and prevention was assessed as a necessary precondition. Sixty-nine German coaches (89.9% male, 76.8% holding the highest license level in boxing, fencing, judo or wrestling) took part in an online survey, which focused on the coaches` existing knowledge, doping perceptions, attitudes and prevention needs. The participating coaches in combat sports regard doping as an international problem. Independent of their type of sports, the coaches indicate a very critical position concerning doping attitudes and moral disengagement and indicate a satisfying knowledge concerning doping substances. Support is needed in the handling of supplements which are assumed to have a gateway function to doping. Several coaches request doping prevention on a regular basis that is embedded in their own coaching courses and tailored to their specific needs. Thus, participating coaches in combat sports have favorable preconditions in their interaction with young athletes and for the implementation and further expansion of doping prevention measures. Effectiveness of coaches` doping prevention needs to be evaluated.